(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to identify the effect of Baska style on students’ achievement and the creative thinking in material rhetoric and the application of students for fifth grade literary. To achieve the study objectives, the researcher has designed an achievement test to measure group of students in the fifth grade literary in material application. The researcher chose a sample of 40 female students from Khansa School for Girls in Baghdad for the academic year (2014 - 2015), he applied the test on an exploratory sample consisted of 30 female students from the research community. The study resulted in being no statistically significant difference at the level of significance (0.05) between the mean scores of the experimental group and control group who taught by the traditional way. The results showed that the style of (Backsa) lifts the capacity of students and adjusts their thinking processes in what they are doing from the tasks that reflect their performance and think to achieve the goal. The use of the method (Backsa) during the presentation of material in rhetoric for the students of the fifth-grade literary lessons helped to clarify the lessons comprehensively. The researcher recommended the adoption style (Backsa) in teaching rhetoric and practice. Involving the Arabic language teachers in training programs about the modern methods especially the method of (Backsa).